A Transforming Public Services Towards Smart City in the Perspective of E-Government in Indonesia - Sukron Makmun, Sukron Makmun; Agus Suharsono, Agus Suharsono; Rohim; MZ Muttaqin (Electronic Journal of Social and Political Sciences (E-SOSPOL), 2025)
The development of digital technology has brought significant changes in various aspects of life, including public services. In the digital era, people demand faster, transparent, and more efficient services. This encourages the government to transform public services by utilizing information and communication technology (ICT). This Transformation of manual systems into digital ones also improves business processes, increases accountability, and ensures community involvement in policymaking. This study uses a qualitative method with a case study approach. The researcher collects data through observation, data analysis, literacy studies, and/or literature review studies. Implementing public policies using smart cities with an e-government system in Indonesia still faces various multidimensional obstacles. The main problems identified include digital access disparity, limited network infrastructure, large implementation budgets, lack of public understanding, linguistic and technical competence barriers, cybersecurity issues, and rejection of digital Transformation.